2008
DOI: 10.1111/j.1365-2583.2008.00840.x
|View full text |Cite|
|
Sign up to set email alerts
|

The hsp27 gene of the Mediterranean fruit fly, Ceratitis capitata: structural characterization, regulation and developmental expression

Abstract: In the present study, a genomic DNA clone encoding the medfly homolog of Drosophila melanogaster hsp27 gene, named Cchsp27, was isolated. We sequenced a part of the clone containing the coding region, the 5' untranslated region and approximately 2.8 Kb of the 5' flanking region of the gene. Phylogenetic analysis of several insect small heat shock proteins, suggested that CcHsp27 is orthologous to Drosophila Hsp27 and Sarcophaga crassipalpis Hsp25. The Cchsp27 gene was mapped at the 81A division of the sixth ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 85 publications
(126 reference statements)
5
27
0
5
Order By: Relevance
“…Previous phylogenetic analysis that included vertebrates and plants has already suggested that different sHSPs of the same species are phylogenetically closer than homologous sHSPs between species, pointing to the possibility that sHSPs might have evolved by gene duplication after species divergence (de Jong et al 1993). However, more recent studies have indicated that several mammalian sHSPs have clearly recognizable orthologs in lower vertebrates (Franck et al 2004), while the HSP27 homologs from D. melanogaster, C. capitata, and S. crassipalpis have been separated from other dipteran sHSPs (Kokolakis et al 2008). In agreement with these data, we found that the HSP27 of C. riparius was also separated from other dipteran sHSPs, suggesting that the four proteins are orthologous and may have evolved before divergence of these species.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Previous phylogenetic analysis that included vertebrates and plants has already suggested that different sHSPs of the same species are phylogenetically closer than homologous sHSPs between species, pointing to the possibility that sHSPs might have evolved by gene duplication after species divergence (de Jong et al 1993). However, more recent studies have indicated that several mammalian sHSPs have clearly recognizable orthologs in lower vertebrates (Franck et al 2004), while the HSP27 homologs from D. melanogaster, C. capitata, and S. crassipalpis have been separated from other dipteran sHSPs (Kokolakis et al 2008). In agreement with these data, we found that the HSP27 of C. riparius was also separated from other dipteran sHSPs, suggesting that the four proteins are orthologous and may have evolved before divergence of these species.…”
Section: Discussionsupporting
confidence: 81%
“…The second domain (aa D 37 -N 49 in ChrHSP27) shows around 50 % amino acid sequence identity among the four HSP27 homologs. This domain is very specific as it is only conserved in the HSP27 (Kokolakis et al 2008), suggesting that it may play a distinct role in this protein. The third domain, located downstream to the α-crystallin domain, contains 28 amino acids (aa K 159 -K 186 in ChrHSP27) and shows around 50 % amino acid sequence identity among the four HSP27 homologs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They share significant sequence similarity and are coordinately expressed following stress, but they have distinct developmental expression patterns and intracellular localizations (Michaud et al 2002). Recently, a few members of the α-crystallin/sHSP family have been cloned from other insect species, including Plutella xylostella (Sonoda et al 2006), Mamestra brassicae (Sonoda et al 2007), Ceratitis capitata (Kokolakis et al 2008), Sesamia nonagrioides (Gkouvitsas et al 2008), Liriomyza sativa (Huang et al 2009), and Macrocentrus cingulum (Xu et al 2010).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…An online protein 3D structure prediction tool (http://swissmodel.expasy.org/) was also used in the structural analysis. Multiple sequence alignments were performed using the Clustal X program with its default parameters (Kokolakis et al 2008). Phylogenetic and molecular evolutionary analyses were performed using the neighbor-joining method with the Molecular Evolutionary Genetics Analysis (MEGA version 4.1) software.…”
Section: Bioinformatic and Phylogenetic Analysesmentioning
confidence: 99%